THE EFFECTS OF SOME IONOPHORE COCCIDIOSTATS ON THE INDEX OF DIGESTIVE TRACT WEIGHT OF BROILERS - Amelia Hana (Jurnal Sain Veteriner, 1999)
Coccidiosis is one of the problems in poultry husbandry since it causes a lot of loss. Nowadays, several ionophore coccidiostats have been used to prevent coccidiosis. However, because of some complaints for ionphore coccidiostats usage, especially Monensin which effect to the weight of digestive tract, therefore the use of coccidiostats should be taken with care. This investigation is intended to undestand the Increase of weight and some changes in digestive tract because of the use of 4 ionophore coccidiosis.This investigation used 52 Hubbard broiler of 1 days age. After 2 weeks of adaption 4 broiler were taken randomly as a control group (without coccidiostat). and the remaining 46 broilers were divided randomly into A group, that is. Monensin (Mo). Karacin (Na). Salinomicin (Sal), and Maduramicin (Mad)- The Mo group was divided futher into 3 subgroups, those are Mo 70, Mo 110, and mo 130 that were fed containing Monensin 70, 110. and 130 mg/kg feed. The other groups were also divided similarly into 3 subgroups, those are, Na 50, Na 70. Na 90; Sal 40, Sal 60, Sal 80; and Mad 4, Mad 5, Mad 6. Number after the abbreviation of coccidiostats indicated the amount of mg/kg reed. The coccidiostats were used to the broilers since 14 until 45 days old. and finally all of the broilers were Killed 4 days later.Using variance analysis with split plot pattern showed that all of the coccidiostats did not effect to the weight growth of broilers (the weighting of broilers was carried out every week since 14 until 49 days old). The use of orthogonal polynomial contrast test indicated that the Monensin coccidiostat effected to the index (the related organ weight/the total weight x 100%) of praventriculus to Cloaca by an equation of VA = 26,9736 - 0,4602 X + G,0024X^P therefore the suggested dosage is 96,53 mg/kg feed. For the Maduramicin coccidiostat. besides it effected to the index of proventriculus-to cloaca by an equation of VR = -12.790 + 7,461 X - 0.696 X*. it also effected to the inffex of duodenum to cloaca by an equation of yc = -5,910+3,585 X - 0.315 X * therefore the suggested dosage is 4 mg/kg feed. The use of Naracin and Salinomicin did not influence to the Index of tractdigestive. All of the coccidiostats did not effect on the thickness of duodenum, jejunum, and ileum. covering diameter (by macroscopic measurement), also the indexes of epithelium/villi weight, mucosa layer thickness, and mus-culer layer thickness that measured by microscopic method-From this investigation can conlcuded that the use of Monensin in 96,53 mg/kg feed. Naracin In 50-90 mg/kg feed, Salinomicin in 40-80 mg/kg feed, and Maduramicin in 4 mg/kg feed will be safe, which means that they willnot increase the weight of tractusgastrointestine.